Computational and experimental evaluation of the mechanical properties of ankle foot orthoses: A literature review. (June 2019) - Ielapi, Alessio; Forward, Malcolm; De Beule, Matthieu
Background: Ankle foot orthoses are external medical devices applied around the ankle joint area to provide stability to patients with neurological, muscular, and/or anatomical disabilities, with the aim of restoring a more natural gait pattern. Study design: This is a literature review. Objectives: To provide a description of the experimental and computational methods present in the current literature for evaluating the mechanical properties of the ankle foot orthoses. Methods: Different electronic databases were used for searching English-language articles realized from 1990 onward in order to select the newest and most relevant information available. Results: A total of 46 articles were selected, which describe the different experimental and computational approaches used by research groups worldwide. Conclusion: This review provides information regarding processes adopted for the evaluation of mechanical properties of ankle foot orthoses, in order to both improve their design and gain a deeper understanding of their clinical use. The consensus drawn is that the best approach would be represented by a combination of advanced computational models and experimental techniques, capable of being used to optimally mimic real-life conditions. Clinical relevance: In literature, several methods are described for the mechanical evaluation of ankle foot orthoses (AFOs); therefore, the goal of this review is to guide the reader to use the best approach in the quantification of the mechanical properties of the AFOs and to help gaining insight in the prescription process.